Topical interferon alpha 2b in the treatment of refractory pseudophakic cystoid macular edema - Arash Maleki; Hossein Aghaei; Stacey Lee (American Journal of Ophthalmology Case Reports, 2018)
Purpose: To report the efficacy and safety of interferon alpha 2b in the treatment of pseudophakic cystoid macular edema resistant to conventional therapy. Observations: A 64-year-old patient presented with pseudophakic cystoid macular edema in her left eye, which developed two months after an uncomplicated cataract surgery and was resistant to multiple topical NSAIDs and multiple intravitreal bevacizumab injections over the course of nine months. She also developed side effects to oral acetazolamide and intravitreal triamcinolone injection; a skin rash and a rise in intraocular pressure (34 mmHg), respectively. She was subsequently started on topical interferon alpha 2b (1 MIU/ml) four times a day nine months after developing pseudophakic cystoid macular edema. Cystoid macular edema improved significantly in four weeks and completely resolved after twelve weeks. Her vision improved from 20/100 before starting treatment to 20/25 twelve weeks after starting treatment. Macular structure and visual acuity were stable throughout a thirty-six weeks follow-up period. Conclusions: and Importance: This case report displays the potential efficacy and safety of interferon alpha 2b in the treatment of refractory cystoid macular edema after cataract surgery. Ocular surface irritation was the only reported adverse effect of the treatment in our patient, this responded to lubricants. Keywords: Cystoid macular edema, Interferon α2b, Pseudophakia